Factors Associated With Farmers' Participation in Community Listening to Farm Broadcast in Central Region, Nepal - Phuyal, Upendra Prasad (1986)
The primary purpose of this study was to determine the relation of some characteristics, selected factors such as demographic communication behaviours, attitude and organizational effectiveness with the level of members' participation in community listening. A secondary purpose was to identify the problems associated with community listening and to find out the farmers' views on the comprehensibility, relevancy and usefulness of farm broadcast programme of the Agricultural In formation Section of the Department of Agriculture, Nepal. The respondents for this study were 105 members of the community listening centres (cue) from nine villages in three selected districts. Data were collected by interviewing the randomly selected respondents in the sample areas. Members' attitudes and perceptions toward cue were measured using 12 items and 6 items Likert-type scale respectively. A total of 12 hypotheses were tested. Pearson product-moment correlation and chi-square were used to test the hypotheses while frequencies and percentages were used for other descriptive analyses. The study revealed that, in general, the level of participation in community listening programme among members of CLC was low. Participation was analyzed with each of the independent variables separately to ascertain the direction and degree of association. The variables such as extension contact, organizational membership, opinion leadership status, message relevancy, attitudes and perceived organizational effectiveness were found to be related positively with the level of participation. Other variables such as age, level of education, family size, farm size and cosmopoliteness were found not significantly related to the level of participation. The results of this study suggest that extension contact, organizational membership, opinion leadership status, message relevancy, attitudes and perceptions are the good indicators of participation.